Strategic shifts in discourse by the AKP in Turkey, 2002 – 2015 - Shukri, Syaza Farhana Mohamad; Hossain, Ishtiaq (Duke University Press, 2017)
This essay identifies and analyzes the AKP’s stated mission and objectives as the party has evolved. The main objective is to discover if there have been any major shifts in the party’s discursive strategy on Islam in an evolving country affected by the political strength of the dominant party. As the AKP grows in strength, one can see that the leaders are becoming bolder in mixing religion with politics. This essay aims to explain how that message has been conveyed and translated to the masses. This is important because,regardless of the words or actions taken by any member or leader of the party,the words used in official party documents can limit actions that stray from the party line.